OMENTAL LIPOBLASTOMA - Mallick, Mohammad Saquib (Journal of Ayub Medical College Abbottabad, 2007)
Lipoblastoma is a rare benign tumour of embryonal fat that occurs almost exclusively in infants and children. It has an excellent prognosis despite its potential to local invasion and rapid growth. Asymptomatic abdominal mass, progressive abdominal distension and intraperitoneal radiolucent fat density mass on computed tomography are the main diagnostic criteria for omental lipoblastoma. This tumour presents in two forms: a localized well-circumscribed lesion (lipoblastoma) or a multicentric type (lipoblastomatosis). Treatment is surgical excision. An unusual case of omental lipoblastoma in a 2-year-old girl is presented in this report. Keywords: Lipoblastoma, omental tumour, total excision.